2022
DOI: 10.3389/fdgth.2022.847991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Therapeutic Alliance With a Free-Text CBT Conversational Agent (Wysa): A Mixed-Methods Study

Abstract: The present study aims to examine whether users perceive a therapeutic alliance with an AI conversational agent (Wysa) and observe changes in the t‘herapeutic alliance over a brief time period. A sample of users who screened positively on the PHQ-4 for anxiety or depression symptoms (N = 1,205) of the digital mental health application (app) Wysa were administered the WAI-SR within 5 days of installing the app and gave a second assessment on the same measure after 3 days (N = 226). The anonymised transcripts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 66 publications
3
43
0
1
Order By: Relevance
“…Considering this, users may have developed a relational connection or a therapeutic alliance with the CA. For example, a recent study demonstrated that Wysa for Chronic Pain users’ therapeutic alliance scores were comparable to ratings from previous studies on alliance in human-delivered face-to-face psychotherapy with clinical populations [ 25 ].…”
Section: Discussionmentioning
confidence: 55%
“…Considering this, users may have developed a relational connection or a therapeutic alliance with the CA. For example, a recent study demonstrated that Wysa for Chronic Pain users’ therapeutic alliance scores were comparable to ratings from previous studies on alliance in human-delivered face-to-face psychotherapy with clinical populations [ 25 ].…”
Section: Discussionmentioning
confidence: 55%
“…Additionally, Wysa has been found to improve mental health outcomes in chronic conditions [ 20 , 21 ], with high engagement and adherence [ 22 ]. It was found that users were able to establish a strong therapeutic alliance with the AI-based conversational agent that was comparable to a human therapeutic bond [ 23 ], further confirming the positive feedback from users [ 24 ]. During the pandemic, Wysa also released 2 tool packs (or intervention packages) named “Health Anxiety” and “Remote Wellness,” which were contextualized to the pandemic.…”
Section: Methodsmentioning
confidence: 78%
“…The research on chatbots for mental health problems in adults has shown that chatbots can produce some unique effects compared to other digital interventions. Users are able to engage and bond with chatbots ( 14 16 ) and tend to humanize and perceive the chatbot as their friend ( 17 ). Users have found mental health chatbots to be helpful, informative, easy to use ( 13 ), and have reported that chatbots are more accepting and not as judgemental as humans ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some users have reported feeling frustration when the chatbot misunderstands them ( 25 ) and found it difficult to connect with them ( 26 ). Retaining and engaging users with chatbots is often challenging ( 14 ) and some people are still reluctant to use chatbots due to stigma ( 16 , 26 ).…”
Section: Introductionmentioning
confidence: 99%